Differentiation of conjunctiva mesenchymal stem cells into secreting islet beta cells on plasma treated electrospun nanofibrous scaffold. (31st October 2018) - Nadri, Samad; Barati, Ghasem; Mostafavi, Hossein; Esmaeilzadeh, Abdolreza; Enderami, Seyed Ehsan
Abstract: Transplantation of stem cells using biocompatible nanofibrous scaffolds is a promising therapeutic method for treating Diabetic Mellitus. The aim of this study was to derive insulin-producing cells (IPCs) from conjunctiva-derived mesenchymal stem cell (CJMSCs) and to compare the functionality of differentiated IPCs in a three-dimensional (3D) culture with 2D. Furthermore, the effects of hydrophobicity of scaffold on IPCs differentiation were examined. Scanning electron microscopy (SEM), quantitative real times PCR (qPCR), Immunostaining and flow cytometry were used to analyze fabricated scaffold and the presence of IPCs. Functional maturity of differentiated cells was determined by measuring insulin release and the creation of IPCs was confirmed via gene and protein expression. In this study, the induced CJMSCs were morphologically similar to pancreatic islet-like cells. The expression of the islet-associated genes (glucagon, insulin and Pdx-1) and the insulin release (2.5-fold) in 3D-cultured cells was significantly higher than the 2D. The expression of IPCs genes was significantly higher in CJMSCs differentiated on plasma-treated nanofibers compared to those on untreated scaffolds. In conclusion, the results show that CJMSCs might be a new source for Diabetic Mellitus therapy and the nanofibrous scaffold could be used as a potential cell carrier for islet tissue engineering.